OPTIMALISASI PERAN PERPUSTAKAAN DALAM MENINGKATKAN MINAT BACA PESERTA DIDIK DI MTS NEGERI 1 PRABUMULIH - Nuria Febriyana; Ratu Wardarita; Siti Rukiyah (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2021)
Indonesian children's interest in reading is still relatively low. The development of students' reading interest in school cannot be separated from the role of the library as a place where students can read and learn. However, the role of the library at MTs Negeri 1 Prabumulih is not maximized. It is proven by the small daily visitor list. This study will seek to optimize the role of the library in increasing students' reading interest using qualitative descriptive research methods with observation methods. Optimization is carried out by promotion, socialization, and collaboration with Indonesian language teachers. The results showed that the reading interest of students at MTs Negeri 1 Prabumulih increased as seen from the library visitors becoming more crowded as evidenced by the visitor book list which showed an increase from 100-250 visitors to more than 300 visitors who come during breaks and there is a regular schedule of library visits for each seventh grade. Keywords: Library, reading interest, student